Pengenalan Media Pembelajaran Ular Tangga Pada Mata Pelajaran IPA Bagian Tubuh Manusia di Kelas II SD Negeri 15 Kumanih Ateh - Mariati, Sari; Hazmi, Merinda; Wulandari, Novia; Fazira, Nurul Fazira; Fanesa, Fani; Azmi, Amira; Buulolo, Silvia Magdalena; Maqrisa, Vionny Wira; Zarifah, Nabilla Darma Nur; Monalisa, Dinda; Aqilah, Nabila Siti; Solina, Anisa Azzahra; Nigrum, Revani Ayu (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2024)
This article discusses the introduction of snakes and ladders learning media in science subjects that focus on human body parts in class II of SD Negeri 15 Kumarih Ateh, located in Pintu Angin Hamlet, Tumpuk Tangah Village, Talawi District, Sawahlunto Regency, West Sumatra Province. This activity was carried out as part of the Community Service Program (KKN) which aims to improve students' understanding of the structure and function of human body parts in an interactive and fun way. Snakes and ladders learning media was chosen because it can increase students' interest in learning and help them remember information through games. The methods used in this introduction include direct delivery of material, snakes and ladders games, and group discussions. Students are invited to actively participate in games that require them to answer questions about human body parts in order to continue the game. The results of this activity indicate that the use of snakes and ladders learning media can increase student involvement, as well as their understanding of science materials. In addition, students showed high enthusiasm during the teaching and learning process. It is hoped that by implementing this method, science learning in class II can be more interesting and effective, and improve student learning outcomes in understanding basic concepts about the human body